Effects of Various Parameters on the Antioxidant Activities of the Synthesized Heterocyclic Pyrimidinium Betaines - Fatiha Malki; Ali Alouache; Soumia Krimat (Indonesian Journal of Chemistry, 2023)
Betaine derivatives are widely used in cosmetic, industrial uses, biology and other scientific fields. Pyrimidinium betaine is a special class of bioactive heterocyclics. They have interesting antioxidant and free radical scavenging activities. This work aims to examine the influence of some parameters on the antioxidant activity of some synthesized betaines containing pyrimidine ring. Four pyrimidinium betaines: monocyclic, bicyclics, and one with a fatty alkyl chain were synthesized from condensation of 2-aminopyrimidine or amidine derivatives with malonic esters, and their antioxidant capacity was evaluated. The effects of concentration, reaction time and temperature on their antioxidant activities were investigated by three common methods: 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, ferric reducing antioxidant power (FRAP) and β-carotene bleaching. The results showed that all pyrimidinium betaines exhibited antioxidant activities in different assays. In the DPPH and reducing power assays, antioxidant activity increased with concentration, whereas in the β-carotene/linoleic acid system, it increased with temperature. On the other hand, the DPPH assay showed an increase in antioxidant capacity over time, while the β-carotene bleaching assay showed a decrease. These results indicate that the antioxidant activity differs depending on the method used and that the various factors affect the antioxidant activity in a different order.